2020
DOI: 10.1016/j.artd.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

How do cemented short Exeter stems perform compared with standard-length Exeter stems? The experience of the New Zealand National Joint Registry

Abstract: a b s t r a c tBackground: The standard Exeter (Stryker) cemented stem is 150 mm long with standard offsets ranging from 37.5 mm to 56 mm. Exeter short stems of 125 mm are also available in the offsets of 37.5 mm, 44 mm, and 50 mm. In addition, smaller (125 mm or shorter) Exeter cemented stems with offsets of 35.5 mm or less are available. The aim of this study was to examine the New Zealand Joint Registry (NZJR) comparing medium-term survival rates and functional outcomes of standard-length stems with Exeter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This was followed by the visual analog scale (VAS) for both orthopedic and cardiac registries, which measures pain ( n = 14 28 , 43-47 , 50-52 , 54-58 and n = 3, 67 , 88 , 89 respectively). The Oxford knee score ( n = 14) 30-34 , 40 , 41 , 64 , 73-75 , 77 , 85 , 92 and Oxford hip score ( n = 12) 28 , 35-39 , 69 , 70 , 75 , 76 , 78 , 85 were also used frequently by orthopedic registries. Beyond these tools, there was wide variation in tools used.…”
Section: Resultsmentioning
confidence: 99%
“…This was followed by the visual analog scale (VAS) for both orthopedic and cardiac registries, which measures pain ( n = 14 28 , 43-47 , 50-52 , 54-58 and n = 3, 67 , 88 , 89 respectively). The Oxford knee score ( n = 14) 30-34 , 40 , 41 , 64 , 73-75 , 77 , 85 , 92 and Oxford hip score ( n = 12) 28 , 35-39 , 69 , 70 , 75 , 76 , 78 , 85 were also used frequently by orthopedic registries. Beyond these tools, there was wide variation in tools used.…”
Section: Resultsmentioning
confidence: 99%
“…Large NJR studies comparing short and standard Exeter stem survivorship (Exeter V40 and Universal stem systems) for primary THA medium-term outcomes report contrasting outcomes for all cause revision rate. 31 , 32 Choy et al’s 31 Australian NJR (1999 to 2010)-based study demonstrated no significant difference (3.4% vs 3.5% at seven years from implantation). Conversely, Wyatt et al’s 32 review of the New Zealand NJR (1998 to 2018) concluded there was a significantly higher all-cause revision rate for short-stems (0.92/100 vs 0.55/100 components-per year) and specifically for aseptic loosening cohort (19.6% vs 7.2%).…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, Wyatt et al’s 32 review of the New Zealand NJR (1998 to 2018) concluded there was a significantly higher all-cause revision rate for short-stems (0.92/100 vs 0.55/100 components-per year) and specifically for aseptic loosening cohort (19.6% vs 7.2%). Interestingly, Wyatt et al 32 reported no femoral implant fractures (41,854 THAs), whereas Choy et al 31 reported ten standard stem (0.03%) and one short stem (0.07%) fractures (36,266 THAs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study looking at the New Zealand National Joint Registry also investigated outcomes of short Exeter stems, but did not specifically look at the 44/00/125 revision stem which is the focus of our study. 22 The introduction of the Exeter short stem line extension in 2014 has led to further studies looking at outcomes of these. It is important to emphasize that these short stems with varying geometry and offset are different from the focus of our study, which is the 44/00/125 cement-in-cement revision stem.…”
Section: Discussionmentioning
confidence: 99%